Analysis of In-service and Pre-service Teachers’ Understanding of Some Concepts of Biotechnology in Biology Curriculum - Sharma, Preeti; D, Avinash; Farkya, Sunita (SCHOOL SCIENCE, 2018)
The emergence of multidisciplinary approaches has always benefited science with newer discoveries. Biotechnology which has tremendous applications with many possibilities should be introduced to students efficiently for their better vision of the subject. The purpose of this study is to analyse the in-service and pre-service teachers about their awareness regarding the latest additions in the field of biotechnology. In order to assess, a questionnaire was developed and the responses from both categories were thoroughly analysed with descriptive statistics. It was observed that the pre-service teachers have a better understanding of the biotechnological concepts than those in-service teachers. Considering the fact that pre-service teachers are in their studying phase, it is interpreted that this category of teachers is trained with an updated syllabus compared to the other. This might be an addition that helps them to be updated. The in-service teachers having good exposure to the older syllabus lack awareness regarding topics from the latest Biotechnological applications. Poor capacity-building programmes and fewer chances for proper up-gradation are some of the barriers for the teachers who are already in service. The addition of biotechnological concepts in the syllabus and improved capacity-building programmes might help to improve the awareness of the pre-service and inservice teachers, respectively